Effects of Fructose and Tapioca Flour on physical and Sensory Properties of Chocolate Bar - Misnawi Jati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
High sucrose content in chocolate is not recommended for diabetics, whereas fructose is a simple monosaccharide which is sweeter and safer for replacing sucrose. Objective of this study was to study the effect of fructose and tapioca flour added into chocolate formulation replacing sucrose on physical and organoleptic properties of chocolate bar produced, as well as to find out their optimum concentration to produce a good quality chocolate. Response Surface Methodology design was used for the study with fructose and tapioca flour range concentration at 141–235 and 25–100 g kg-1, respectively. Results of the study showed that fructose and tapioca flour concentration at the stated ranges did not significantly alter the chocolate properties except on chocolate particle size and preferences in terms of taste, aroma and overall acceptance. Fructose concentration improved particle size quadratically, while tapioca flour concentration linearly decreased taste, aroma and overall acceptance scores. Comparing the products with that of control formula concluded that fructose can be used to replace sucrose to produce good quality chocolate bars; while tapioca flour can be used as filler at a concentration up to 25 g kg-1. The optimum concentration to formulate chocolate bars with good physical and organoleptic properties was at fructose and tapioca flour concentration of 203 and 25 g kg-1, respectively. Key words: Cocoa, chocolate, fructose, diabetes, tapioca flour, flavour, aroma, texture